Involvement of interleukin-1 (IL-1), IL-6, IL-2, and IL-4 in generation of cytolytic T cells from thymocytes stimulated by a Mycoplasma fermentans-derived product. - Mühlradt, P F (1991)
The capacity of Mycoplasma fermentans-derived high-molecular-weight material (MDHM) to generate cytolytic T cells from mitogen-stimulated murine thymocytes was studied in detail. The role of MDHM and the involvement of monokines and lymphokines resulting from the addition of MDHM to thymocyte cultures were examined in complete and adherent cell-depleted culture systems by the addition of neutralizing monoclonal antibodies against interleukin-2 (IL-2), IL-4, and IL-6 and in reconstitution experiments with recombinant mediators. The data presented here suggest that MDHM is crucial only in the first phase of a reaction sequence beginning with the stimulation of adherent accessory cells and resulting in the synthesis of IL-1 and IL-6. The lymphokines IL-2 and, primarily, IL-4 are required in a second step which, once these lymphokines are formed, can proceed in the absence of MDHM and accessory cells and leads to the formation of cytolytic T cells. The elucidation of the MDHM-induced reaction sequence may be of relevance in view of the hypothetical role of mycoplasmas in rheumatic disease in humans. M. fermentans is an organism capable of infecting humans and in an early report has been discussed as a causative agent for rheumatoid arthritis.